2019
DOI: 10.1016/s1470-2045(19)30420-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine treatment versus chemotherapy in postmenopausal women with hormone receptor-positive, HER2-negative, metastatic breast cancer: a systematic review and network meta-analysis

Abstract: Background Although international guidelines support the administration of hormone therapies with or without targeted therapies in postmenopausal women with hormone-receptor-positive, HER2-negative metastatic breast cancer, upfront use of chemotherapy remains common even in the absence of visceral crisis. Because first-line or second-line treatments, or both, based on chemotherapy and on hormone therapy have been scarcely investigated in head-to-head randomised controlled trials, we aimed to compare these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 38 publications
10
100
1
14
Order By: Relevance
“…Another recent and very large network meta-analysis has evaluated all chemotherapy and ET-based treatments in postmenopausal women with HR+/HER2− metastatic breast cancer. 80 Similarly to our results, it has showed that CDK4/6i plus ET are better than standard ET; in addition, it has demonstrated that no chemotherapy regimen was significantly better than CDK4/6i plus ET in terms of PFS. However, this network meta-analysis did not include premenopausal women, did not provide OS data or analysed efficacy according to endocrine-sensitivity status or different patients' subgroups (visceral disease, bone-only, etc).…”
Section: Discussionsupporting
confidence: 88%
“…Another recent and very large network meta-analysis has evaluated all chemotherapy and ET-based treatments in postmenopausal women with HR+/HER2− metastatic breast cancer. 80 Similarly to our results, it has showed that CDK4/6i plus ET are better than standard ET; in addition, it has demonstrated that no chemotherapy regimen was significantly better than CDK4/6i plus ET in terms of PFS. However, this network meta-analysis did not include premenopausal women, did not provide OS data or analysed efficacy according to endocrine-sensitivity status or different patients' subgroups (visceral disease, bone-only, etc).…”
Section: Discussionsupporting
confidence: 88%
“…After that, newer effective treatment strategies based on CDK4/6 inhibitors combined with aromatase inhibitors or fulvestrant and the PI3K inhibitor alpelisib combined with fulvestrant for PIK3CA-mutant patients have also been added to the therapeutic armamentarium in the last few years [ 35 – 37 ]. A recent comprehensive network meta-analysis highlighted comparable therapeutic performances between such therapies and chemotherapy [ 38 ]. However, at present, the optimal treatment sequence is not known, as there is a lack of direct comparisons and no effective biomarkers of response for all these treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In women, breast cancer represents nearly one-third of newly diagnosed cancers and is the most common cancer in women from ages 20 to 59 (1). Currently, breast cancer treatments are based on the expression of biomarkers, such as progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor 2 (EGFR2, also known as HER2) (1,2). Good clinical outcomes have been observed after anti-hormonal therapies in tumors expressing ER, although these therapies lead to resistance, limiting the effectiveness of hormone-based therapy (3).…”
Section: Introductionmentioning
confidence: 99%